2023
DOI: 10.1108/jcms-04-2023-0014
|View full text |Cite
|
Sign up to set email alerts
|

Alternatives to the efficient market hypothesis: an overview

Kingstone Nyakurukwa,
Yudhvir Seetharam

Abstract: PurposeThe authors’ goal is to provide an overview and historical context for the various alternatives to the efficient market hypothesis (EMH) that have emerged over time. The authors found eight current alternatives that have emerged to address the EMH's flaws. Each of the proposed alternatives improves some of the assumptions made by the EMH, such as investor homogeneity, the immediate incorporation of information into asset values and the inadequacy of rationality to explain asset prices.Design/methodology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…The premises of perfect rationality are understood as a descriptive approach that prescribes how decision-makers should behave, but not how they actually do (Sent, 2018). The recent systematic review by Nyakurukwa and Seetharam (2023) concluded that rationality is a dynamic concept that is the best understood with a multidisciplinary approach, combining concepts, theories, and ideas from a variety of disciplines, including physics, economics, anthropology, and sociology.…”
Section: The Types Of Investor Rationalitymentioning
confidence: 99%
“…The premises of perfect rationality are understood as a descriptive approach that prescribes how decision-makers should behave, but not how they actually do (Sent, 2018). The recent systematic review by Nyakurukwa and Seetharam (2023) concluded that rationality is a dynamic concept that is the best understood with a multidisciplinary approach, combining concepts, theories, and ideas from a variety of disciplines, including physics, economics, anthropology, and sociology.…”
Section: The Types Of Investor Rationalitymentioning
confidence: 99%